Rethinking Explanation - Persson, Johannes; Ylikoski, Petri (Springer, 2007)
This volume is a product of the international research project Theory of Explanation,which was funded by the Joint Committee for Nordic Research Councils for the Humanities and the Social Sciences (NOS-HS). The project started in 2001 and operated for a period of three years by organizing a number of workshops on scientific explanation in Norway, Iceland, Sweden and Finland. The workshops included presentations by people involved in the project and by invited guests. Both groups are represented in this volume, which brings together some of the papers presented in these meetings. The central theme of the research project was scientific explanation, but it was approached from many different angles. This plurality of approaches is also visible in the present volume. The authors share a joint interest in explanation, but not the same theoretical or methodological assumptions. As a whole, this volume shows that, although the theory of explanation has been a major industry within philosophy of science, there are still both conceptual problems to be solved and fresh philosophical ideas to explore. The papers in this volume have been divided into two broad groups. Part 1 consists of papers dealing with general issues in the theory of explanation, while the papers in Part 2 focus on some more specific problems.